Well Water Quality Assessment Around Ciangir Landfill, Tasikmalaya City, Using the Pollution Index - Tegar Muhammad Mikdar; Melly Mellyanawaty (Indonesian Journal of Chemistry and Environment, 2026)
Shallow groundwater around landfill should be monitored because landfill leachate may transport dissolved solids, organic matter, and metals into residential water sources. This study evaluated well water quality around the Ciangir Landfill, Tasikmalaya City, using pH, temperature, iron (Fe), manganese (Mn), and turbidity, and determined water quality status using the Pollution Index. Nine wells were purposively selected at 0 m, 50 m, and 100 m from the landfill area and were sampled during dry and rainy seasons. The results showed that pH was acidic at several points, while Fe generally remained below the 1 mg/L standard. Mn exceeded the 0.5 mg/L standard at point A1, particularly in the dry season, and high turbidity occurred at several points during the rainy season. The average Pollution Index was 0.8991, indicating compliance with the standard, although the dry-season value reached 1.0394 and was classified as slightly polluted. Periodic monitoring and improved leachate management are required to prevent further deterioration of local well water.